Energia e nutrientes digestíveis de alimentos para a tilápia do nilo - Goncalves, Giovani Sampaio; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP]; Rocha, Dario Falcon [UNESP]; Kleeman, Geisa Karine [UNESP]; Santa Rosa, Maria Julia (Inst Pesca, 2009)
The utilization of energetic and protein feeds, highly digestible as well, becomes more and more necessary due to the quality of formulated rations, fish performance and relationship with the environment. Apparent digestibility coefficient (ADC) of dry matter, protein, energy, phosphorus, and amino acids of corn starch, corn, wheat, rice, soybean, and cottonseed meal, corn gluten and fish meal were determined for Nile tilapia. ADC was determined using a reference diet based on albumin, gelatin and corn starch, was used inert indicator chromium III oxide (Cr(2)O(3)). Each test diet composed by 70% of reference diet and 30% of the test diet. Feces were collected using mofied Guelph system. ADC values for protein and average ADC of amino acids were as follows: corn 89.76 and 96.43%, rice meal 95.88 and 92.26%, wheat meal 93.54 and 84.41%, fish meal 82.59 and 86.36%, corn gluten 89.82 and 87.98%, soybean meal 94.13 and 91.93%, cotton meal 87.10 and 77.47%, respectively. According to the results of this work, ADC of protein is not a reliable indicator of ADC values of amino acids, even more so for wheat meal, corn, and cotton meal. Among protein feeds, soybean meal was found to have the highest ADC for protein and amino acids, while corn was the energetic feed with the highest ADC (86.15%) for energy.
Digestible nutrients of nile tilapia feed
Keywords: amino acids; digestibility; energy; nutrition; Nile tilapia